Parent–child conversations associated with alcohol-related risk behaviours in young people (13–17 years) in the UK: a cross-sectional study. Issue 6 (17th June 2020) - Jones, Anna-Marie; Sawyer, Alexandra; Huber, Jörg W; Coleman, Lester; Dunne, Nina; Sherriff, Nigel
Abstract : Objective: To investigate different types of parent–child conversations associated with young people's (13–17 years) alcohol-related risk behaviours. Design: Secondary analysis of the 2016 Drinkaware Monitor Survey. This survey employed a cross-sectional design and collected data using self-completion questionnaires. Setting: UK-wide. Participants: 561 parent–child pairs were included in the analysis. The nationally representative quota sample was weighted by reference to the UK population. Methodology: Data were analysed using purposeful selection modelling (adjusted OR (AOR), 95% CIs). Risk behaviours: 'Whether have ever drank' and 'whether vomited as a result of alcohol'. Results: 50% (277/553) of young people reported drinking a whole alcoholic drink, and 22% (60/277) of these experienced vomiting as a result. After adjusting for age and gender, the likelihood of ever having drank alcohol was significantly increased among the following young people: those whose parents believed they knew a little about how much they drink (AOR 1.80, 95% CI 1.04 to 3.13) or that some/most/all friends drink (AOR 3.82, 95% CI 2.40 to 6.08); those given gentle reminders about taking care when drinking alcohol (AOR 1.82, 95% CI 1.15 to 2.88), practical advice (AOR 2.09, 95% CI 1.20 to 3.64) or designated time, led by the parent, to instil care around alcohol through a formal sit-down (AOR 1.79, 95% CI 1.07 to 2.99). The likelihood was reduced for parents aged 40–49 years (AOR 0.52, 95% CI 0.31 to 0.89) and conversations providing information (AOR 0.53, 95% CI 0.29 to 0.98). Vomiting was significantly associated with some/most/all friends drinking alcohol (AOR 3.65, 95% CI 1.08 to 12.30), parent's beliefs about child's frequency of drinking alcohol (AOR 1.26, 95% CI 1.02 to 1.54), parental harmful/dependency drinking (AOR 3.75, 95% CI 1.13 to 12.50) and having a formal sit-down conversation (AOR 2.15, 95% CI 0.99 to 4.66). Conclusions: We found evidence of mostly negative associations between young people's risk behaviours and different types of parent–child conversations. Conversations providing information were linked to a reduced tendency to have ever drunk alcohol. All other types of conversations were negatively associated with risk behaviours. Psychological reactance and conversation quality possibly explain these findings.